Instrumento de avaliação de HUBs de inovação: métricas de participação no ecossistema empreendedor - Castilho, Letícia Rodrigues Albuquerque de (2025)
This study proposes the development of an evaluation tool to measure the impact of innovation HUBs on the innovative performance of participating companies. The research stems from the recognition of a lack of specific and standardized metrics that allow for an objective assessment of the results generated by these collaborative environments. Grounded in Christensen’s theory of disruptive innovation, the study is structured into three innovation categories: market-creating, sustaining, and efficiency. The methodology adopted is qualitative, descriptive, and exploratory in nature, based on literature reviews and document analysis. The proposed tool consists of a questionnaire organized into thematic blocks, with goals and specific indicators for each type of innovation. The measurement scale enables the evaluation of aspects such as market reach, customer satisfaction, productivity, and return on investment (ROI). As a theoretical and practical contribution, the model aims to support strategic innovation management within HUBs, inform public policies, and foster the professionalization of innovation environments. Empirical application of the tool is recommended in various contexts for validation and refinement.